PROFESSIONAL CONDUCT OF SCIENTISTS DURING VOLCANIC CRISES - Newhall Ch.; Aramaki Sh.; Barberi F.; Blong R.; Calvache M.; Cheminee J.L.; Punongbayan R.; Siebe C.; Simkin T.; Sparks S.; Tjetjep W. (My University, 1999)
Stress during volcanic crises is high, and any friction between scientists can distract seriously from both humanitarian and scientific effort. Friction can arise, for example, if team members do not share all of their data, if differences in scientific interpretation erupt into public controversy, or if one scientist begins work on a prime research topic while a colleague with longer-standing investment is still busy with public safety work. Some problems arise within existing scientific teams; others are brought on by visiting scientists. Friction can also arise between volcanologists and public officials. Two general measures may avert or reduce friction: (a) National volcanologic surveys and other scientific groups that advise civil authorities in times of volcanic crisis should prepare, in advance of crises, a written plan that details crisis team policies, procedures, leadership and other roles of team members, and other matters pertinent to crisis conduct. A copy of this plan should be given to all current and prospective team members. (b) Each participant in a crisis team should examine his or her own actions and contribution to the crisis effort. A personal checklist is provided to aid this examination. Questions fall generally in two categories: Are my presence and actions for the public good? Are my words and actions collegial, i.e., courteous, respectful, and fair? Numerous specific solutions to common crisis problems are also offered. Among these suggestions are: (a) choose scientific team leaders primarily for their leadership skills; (b) speak publicly with a single scientific voice, especially when forecasts, warnings, or scientific disagreements are involved; (c) if you are a would-be visitor, inquire from the primary scientific team whether your help would be welcomed, and, in general, proceed only if the reply is genuinely positive; (d) in publications, personnel evaluations, and funding, reward rather than discourage teamwork. Models are available from the fields of particle physics and human genetics, among others.
Keywords: VOLCANIC CRISES; PROTOCOLS; ETHICS; COMMUNICATION; TEAMWORK